Właściwości psychometryczne kwestionariusza do pomiaru wizerunku konsumenta = Psychometric properties of a questionnaire measuring the image of the consumer - Gorbaniuk, Oleg; Dudek, Marzena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the research was developing scales to measure the image of the consumer based on the previous psycho-lexical studies. 180 people aged 16 to 66 years (49.6% women) described typical consumers of different product brands using a list of 36 adjectives. A total of 1,080 descriptions were gathered.
Keywords: wizerunek konsumenta; podejście psycholeksykalne; konfirmacyjna analiza czynnikowa; walidacja psychometryczna; the image of the consumer; psychometric validity; psycho-lexical approach; multi-level analysis